(3SdSdI GdPgH GdEHQjR h GdEcSjQ GdYRjRs ((3eMe(B-(3O Hf CSYO Hf RjO Hf CMeO GdePMLi s)
(3ChdgG (B:s
(3CNHQfG GdCejQ GdSjO aNQ GdOjf EHQGgje Hf CejQ GdeDefjf YHO Gddg Hf MeRI SfI KdGKjf hSJeGFI ai eSLO GdbGgQI bGd CNHQfG LeGd GdOjf YeQGf Hf GdMSf Hf fGUQ GdYPQi GdgeOGfi s
(3BNQgG (B:s
(3Gddge HGQc dCeJi ai HchQgG jhe GdNejS hHg cGO GdabQ Cf jchf caQkG , hHg GdSaQ bWYg ef GdYPGH hHg NjQ GdRGO GdJbhi hUdi Gddg Ydi eMeO hBdg hSde s
(3CQHYhf MOjKkG HSfO jfJgi ddEeGe Ydi Hf CHj WGdH hChdgG djS GdNHQ cGdeYGjfI hBNQgG NjQ GdRGO GdJbhis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdcjejGA h GdWHjYjGJs